TERNARIOS CATALYTIC SYSTEMS CHARACTERIZATION OF NI , CU AND CRPOR TPR , XPS AND SEM - Muñoz H., Patricio (2006)
n this work, additional characterization of ternary catalysts ( 1) ( NiO, reported CuO/Crp3 w / wi 5 : i, 8 : 1 , 5) and ( 2) ( NiO, CuO/Crp3 w / w 2.2 : 0.6 : 1, 4 ) by TPR , XPS and SEM , which showed better activity in the hidrogenéfión benzene gas tase u. TPR results show the existence of the synergetic effect in the systems ternarios3 . XPS indicated that the metal components in the oxides are as Ni2 + , Cu2 • and Cr ' - except in the catalyst ( 1) the presence of Cr3 is observed at a binding energy of 578.9 eV Finally , the results of SEM micrograph showing the surface composition and atomic percent of the catalysts ( 1) and ( 2) as : ( 37.38% Ni, 38.34 % Cu, 24.28% Cr) and ( 62.44 % Ni, 20.37% Cu, i 7 i 9% Cr ) , respectively